2010
DOI: 10.1136/bjo.2010.189456
|View full text |Cite
|
Sign up to set email alerts
|

Agreement to detect glaucomatous visual field progression by using three different methods: a multicentre study

Abstract: AimTo examine the level of agreement among nine clinicians in assessing progressive deterioration in visual field (VF) overview using three different methods of analysis. Methods Each visual field was assessed by Humphrey Field Analyzer (HFA), program 24-2 SITA Standard. Nine expert clinicians assessed the progression status of each series by using HFA 'overview printouts' (HFA OP), the Guided Progression Analysis (GPA) and the Guided Progression Analysis (GPA2). VF series were presented in random order, but e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…28 They reported a median kappa of 0.58 for intra-observer agreement between the session when only the overview printout was available and the session when only the GPA 1 printout was available. They did not report the level of agreement among the expert readers' opinions and the GPA result itself.…”
Section: Discussionmentioning
confidence: 99%
“…28 They reported a median kappa of 0.58 for intra-observer agreement between the session when only the overview printout was available and the session when only the GPA 1 printout was available. They did not report the level of agreement among the expert readers' opinions and the GPA result itself.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 However, most of the current information on the value of software-provided detection of progression comes from the former instrument family. [6][7][8][9][10] The commercially available Octopus software versions (Peritrend, EyeSuite) offer determination of the rate of progression for global mean defect (MD), diffuse defect (DD), local defect, and pointwise linear regression analysis. 11 However, as several core technical features (background luminance, stimulus duration, number and distribution of the test points, and size of the tested central visual field) are different in the Octopus perimeters and Humphrey Field Analyzers, 4,5 experience on progression determined with the Humphrey system cannot be directly applied to Octopus perimetry.…”
mentioning
confidence: 99%
“…A review of reference lists of included full text articles revealed another four articles for inclusion. Three studies which were originally included for data extraction were excluded on closer inspection . Asakawa et al.…”
Section: Resultsmentioning
confidence: 99%